Coupled motion of Xe clusters and quantum vortices in He nanodroplets - Jones, C. F.; Bernando, C.; Tanyag, R. M. P.; Bacellar, C.; Ferguson, K. R.; Gomez, L. F.; Anielski, D.; Belkacem, A.; Boll, R.; Bozek, J.; Carron, S.; Cryan, J.; et al. (My University, 2016)
Single He nanodroplets doped with Xe atoms are studied via ultrafast coherent x-ray diffraction imaging. The diffraction images show that rotating He nanodroplets about 200 nm in diameter contain a small number of symmetrically arranged quantum vortices decorated with Xe clusters. Unexpected large distances of the vortices from the droplet center (?0.7-0.8 droplet radii) are explained by a significant contribution of the Xe dopants to the total angular momentum of the droplets and a stabilization of widely spaced vortex configurations by the trapped Xe clusters. © 2016 American Physical Society.
Citation: Jones, C. F., Bernando, C., Tanyag, R. M. P., Bacellar, C., Ferguson, K. R., Gomez, L. F., . . . Vilesov, A. F. (2016). Coupled motion of Xe clusters and quantum vortices in He nanodroplets. Physical Review B - Condensed Matter and Materials Physics, 93(18). doi:10.1103/PhysRevB.93.180510
Additional Authors: Erk, B.;Foucar, L.;Hartmann, R.;Neumark, D. M.;Epp, S. W.;Englert, L.;Siefermann, K. R.;Weise, F.;Rudek, B.;Sturm, F. P.;Ullrich, J.;Bostedt, C.;Gessner, O.;Vilesov, A. F.